2023
DOI: 10.3390/nu15112600
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation Syndrome of High-Cholesterol-Diet-Induced Hypercholesterolemia in Mice by Intervention with Lactiplantibacillus plantarum WLPL21 via Regulation of Cholesterol Metabolism and Transportation as Well as Gut Microbiota

Abstract: Probiotics are prospective for the prevention and treatment of cardiovascular diseases. Until now, systematic studies on the amelioration of hypercholesterolemia have been rare in terms of (cholesterol metabolism and transportation, reshaping of gut microbiota, as well as yielding SCFAs) intervention with lactic acid bacteria (LAB). In this study, strains of Lactiplantibacillus plantarum, WLPL21, WLPL72, and ZDY04, from fermented food and two combinations (Enterococcus faecium WEFA23 with L. plantarum WLPL21 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…L. plantarum WLPL21 and L. plantarum ZDY04, isolated from Chinese fermented soybeans and pickled vegetables [ 18 ], were cultured under anaerobic conditions at 37 °C in sterile deManRogosa Sharpe (MRS broth; Beijing Solarbio Science & Technology Co., Ltd., Beijing, China) in an anaerobic incubator (GeneScience Anaerobox IV, San Francisco, CA, USA) for 12 h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…L. plantarum WLPL21 and L. plantarum ZDY04, isolated from Chinese fermented soybeans and pickled vegetables [ 18 ], were cultured under anaerobic conditions at 37 °C in sterile deManRogosa Sharpe (MRS broth; Beijing Solarbio Science & Technology Co., Ltd., Beijing, China) in an anaerobic incubator (GeneScience Anaerobox IV, San Francisco, CA, USA) for 12 h.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, L. plantarum WLPL21 and ZDY04 from Chinese fermented soybeans and pickled vegetables, respectively, were shown to play a great role in the alleviation of hypercholesterolemia in a high-cholesterol-diet-induced model in vivo [ 18 ]. However, elucidating its cholesterol-lowering mechanism and the existence of bacteriocin genes still stand as research hurdles.…”
Section: Introductionmentioning
confidence: 99%
“…Specific LAB from fermented fruits and vegetables can reduce serum cholesterol, thereby reducing the risk of cardiovascular disease. L. plantarum WLPL21 and L. plantarum ZDY04, isolated from Chinese fermented soybeans and pickled vegetables showed that their excellent capacity for lowering cholesterol in vivo (Zhao et al, 2024). Fermented vegetables can also control high blood sugar, high blood pressure and regulate gut microbiota health (Niu et al, 2019;Yeon et al, 2019;Mathur et al, 2020;Daliri et al, 2022).…”
Section: Microbial and Health Benefits Of Fermented Vegetablesmentioning
confidence: 99%
“…L. plantarum CCFM1143 alleviated diarrhoea by inflammation regulation and gut microbiota modulation [ 6 ]. L. plantarum WLPL2 decreased high cholesterol and hypercholesterolaemia [ 7 ], and L. plantarum JS19 as well as L. plantarum A3 prevented irritable bowel syndrome symptoms [ 8 , 9 ]. Moreover, crude exopolysaccharides of L. plantarum-12 significantly inhibited the proliferation of colon cancer HT-29 cells and thus showed potential anti-cancer activity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%